The mechanisms of neuroprotective action of p-tyrosol after the global cerebral ischemia in rats - A. N. Osipenko; T. M. Plotnikova; G. A. Chernysheva; V. I. Smolyakova (Бюллетень сибирской медицины)
Aim. The aim of our study is to explore the mechanisms of neuroprotective effects of p-tyrosol in acute global cerebral ischemia-reperfusion in rats.Material and methods. The study was performed on 30 male rats stock Wistar (250–300 g).Animals were divided into 3 groups of 10 rats. In the control and experimental groups we performed the new 3VO model of cerebral ischemia-reperfusion, and the sham-operated animals underwent the same surgical procedures, but without the ligature imposition. Animals in the experimental group received p-tyrosol for 5 days intravenously at a daily dose of 20 mg/kg in a 2% solution. The sham-operated rats and control animals received a isotonic solution of NaCl at the same scheme. We measured rheological blood parameters and the content of products of lipid peroxidation in the brain tissue on the 5th day after cerebral ischemia-reperfusion.Results. Acute ischemia-reperfusion of the brain in rats from the control group caused the significant hemorheological abnormalities, including the increased whole blood viscosity and plasma viscosity, decreased the erythrocyte aggregation half-time and decreased red blood cell deformability index. The increase blood viscosity caused the decrease of the oxygen delivery to the tissues. The content of diene and triene conjugates, fluorescent products and the lipid oxidation index increased in the brain tissue of the control group. These abnormalities induced the death of 50% animals from the control group. Given intravenously to animals of the experimental group, p-tyrosol reduced the whole blood viscosity by 19–31%, the plasma viscosity by 6% and increased the erythrocyte deformability by 31–40%, that led to the increase of oxygen availability for tissues by 21–31% in comparison with the control group. The contents of diene and p-triene conjugates and fluorescent products in the brain tissue under course administration of p-tyrosol decreased respectively by 37%, 49 and 45%, that reflected in the decreasing of lipids oxidation index by 38% in comparison with the control group. The number of survived animals in the experimental group was 1,4 times bigger than in the control group.Conclusion. Course administration of p-tyrosol to rats with acute cerebral ischemia-reperfusion reduces the blood viscosity and the intensity of oxidative stress in the brain tissue. The results of these effects are the reduction of negative outcomes of ischemia-reperfusion of the brain and the increasing of animal surviving, that confirms the neuroprotective action of p-tyrosol in these conditions.